Students' perception of their own self-esteem and improvement of their psychophysiological abilities - Orlov V.A. ,; Strizhakova O.V. ,; Fetisov O.B. , (Theory and Practice of Physical Culture, 2025)
Objective of the study is to assess students' attitudes towards self–esteem and the development of their psychophysical potential. Methods and structure of the study. In accordance with a specially developed methodology, students' behavior was monitored in the process of passing the TRP standards. At the same time, some of their psychological characteristics were evaluated. 46 students of the Stroganov Moscow State Academy of Art and Industry became the object of observation. Results and conclusions. There is a lack of interest among students in self-analysis and evaluation of their psychophysiological and cognitive qualities. Along with this, the results of motor coordination tests revealed that a significant part of the students' level of motor skills development leaves much to be desired, which is probably a consequence of deficiencies in physical development and education received in childhood and adolescence. Probably, many students do not fully realize that modern life and the professional sphere are a continuous struggle for promising positions and a decent standard of living. This aspect of the psychocognitive characteristics of Russian students and young professionals raises concerns and needs a deeper and more thorough study.